Specific Characteristics of Organizing and Conducting International Assessment Programs - Ibadullaev Kahramon Madaminovich (Researchparks Publishing, 2022)
This article analyzes the specific features of organizing and conducting international evaluation programs, innovative methods of teaching that affect the improvement of education in the research conducted by international evaluation programs, the advantages of the educational system of developed countries, and the factors that lead to the decline of education.